2019
DOI: 10.1590/1806-9061-2018-0962
|View full text |Cite
|
Sign up to set email alerts
|

Techniques to Minimize the Effects of Acute Heat Stress or Chronic in Broilers

Abstract: High environmental temperature is limiting factor in broiler production. In order to minimize the undesirable consequences of acute or chronic heat stress, the techniques of fixed dietary electrolyte balance and early heat conditioning were evaluated. The objective of this study was to evaluate the possible interactions and effects of dietary electrolyte balance and early heat conditioning on feed intake, body weight, feed conversion ratio, mortality, energy bioeconomic index, fecal moisture, abdominal fat, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The results of the clinical signs in the HS group are compatible with the results of Li et al ( 33 ) who reported that heat stress significantly affects the daily behavior of broilers, including feeding, drinking, lying, standing, and walking. Moreover, Rodrigues et al ( 34 ) recorded a high percentage of fecal moisture as a result of heat stress. Moreover, the results of the growth were significantly affected by heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the clinical signs in the HS group are compatible with the results of Li et al ( 33 ) who reported that heat stress significantly affects the daily behavior of broilers, including feeding, drinking, lying, standing, and walking. Moreover, Rodrigues et al ( 34 ) recorded a high percentage of fecal moisture as a result of heat stress. Moreover, the results of the growth were significantly affected by heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the effect of on activity between light and dark periods may be caused by several factors. First, birds may display compensatory behavior: during the hottest part of the day, birds may eat less ( Rodrigues et al, 2019 ), and they need to compensate for this when the temperature drops in subsequent periods. This compensatory behavior is reflected in the shift of activity from the light to the dark periods in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…This was surprising, because we expected that birds would move less with higher temperatures to reduce heat production. A possible explanation for this result is that although the birds are prone to move less, they are also motivated to drink more ( Li et al 2015 ; Rodrigues et al, 2019 ; Kim et al 2022 ; Cartoni Mancinelli et al, 2023 ). As a result, they may move to and away from the drinkers more often.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed an increase in mRNA levels of the ACE gene due to acute thermal stress. Although this seems beneficial at first, it is necessary to consider the fact that thermal stress severely alters the hydroelectrolytic balance (Rodrigues et al, 2019). Thus, inadequate Research, Society and Development, v. 9, n. 8, e63985059, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.5059 20 ACE increase followed by increased production of angiotensin II may favor the onset of hypertension and increased cardiovascular morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%